The Development Impact of PT. Medco E & P Malaka on Economic Aspects in East Aceh Regency - Mirza Mardhan Shah; Sirojuzilam Sirojuzilam; Linda T Maas (Budapest International Research and Critics University, 2020)
Development basically aims to realize prosperity for the community. Development can be done by implementing in various forms of programs. Development that uses human resources and high technology to process natural resources that can be utilized for human life, one of which is the development of oil and gas exploration block A area of PT. Medco E & P Malaka in Indra Makmur Sub-district. This activity is expected to provide positive benefits for the welfare of the people around the exploration activities. The type of research is associative research with a quantitative approach. This research was conducted in the oil and gas exploration area of Block A Area PT. Medco E & P Malaka in Alue Ie Itam and Blang Nisam Villages in Indra Makmur Sub-district, East Aceh Regency. Respondents in the study consisted of 50 respondents. The result of this study is the economic impact of oil and gas exploration development in Block A area of PT. Medco E & P Malaka has a very positive impact on income, home ownership, home conditions, and additional income of the community in Alue Ie Itam Village and Blang Nisam Village. This can be seen from tcount (6.852) which is greater than ttable (1.67591). Significant differences are also indicated by the significance score (0.00 <0.05).